Merging arts entrepreneurship and social entrepreneurship: positions, perspectives, and a proposed module outline for higher music education students - Roux, Rone (Stellenbosch : Stellenbosch University, 2025)

(untitled)
Thesis (MMus)--Stellenbosch University, 2025.